Temporal and spatial transcriptional regulation of phytohormone metabolism during seed development in barley (Hordeum vulgare L.) - Tuan, Pham Anh; Nguyen, Tran-Nguyen; Toora, Parneet K.; Ayele, Belay T. (Frontiers in Plant Science, 2023)
Plant hormones play important roles in seed development; however, transcriptional regulation of their metabolism and levels of the respective bioactive forms during barley seed development are poorly understood. To this end, this study performed a comprehensive analysis of changes in the expression patterns phytohormone metabolism genes and levels of the respective bioactive forms in the embryo and endosperm tissues. Our study showed the presence of elevated levels of bioactive forms of abscisic acid (ABA), gibberellins (GAs), auxin, jasmonate (JA), cytokinins (CKs) and salicylic acid (SA) in the endosperm and embryo tissues at early stage of seed filling (SF). The levels of all hormones in both tissues, except that of ABA, decreased to low levels during SF. In contrast, embryonic ABA level increased during SF and peaked at physiological maturity (PM) while the endospermic ABA was maintained at a similar level observed during SF. Although its level decreased to relatively lower level, elevated level of embryonic ABA was still present in the embryo during post-PM. We detected low levels of ABA in the endosperm and all the other hormones in both tissues during post-PM phase except the relatively higher levels of JA-Ile and SA detected at late stage of post-PM. Our data also showed that spatiotemporal changes in the levels plant hormones during barley seed development are mediated by the expression of specific genes involved in their respective metabolic pathways. These results indicate that seed development in barley is mediated by spatiotemporal modulation in the metabolism and levels of plant hormones.